2021
DOI: 10.1007/s11524-021-00588-1
|View full text |Cite
|
Sign up to set email alerts
|

Confidence and Hesitancy During the Early Roll-out of COVID-19 Vaccines Among Black, Hispanic, and Undocumented Immigrant Communities: a Review

Abstract: Black and Hispanic Americans have been hardest hit with COVID-19 infections, hospitalizations, and deaths, yet during the first several months of vaccine roll-out they had the lowest level of vaccine uptake. Primarily, our research on vaccine hesitancy focused on skepticism around the vaccine itself and its roll-out. Our search strategy used PUBMED and Google with a prescribed set of definitions and search terms for two reasons: there were limited peer-reviewed studies during early period of roll-out and real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 28 publications
2
53
1
Order By: Relevance
“…The current paper reports qualitative findings from semi-structured interviews with Black Americans who showed low vaccine confidence as well as stakeholders representing different Black communities during the early stage of the COVID-19 vaccine roll-out. We documented low COVID-19 vaccination intentions (e.g., the need to wait and see) and specific concerns around the COVID-19 vaccines (e.g., about rapid development and side effects), which are consistent with similar qualitative research in racially/ethnically diverse populations (including Black Americans) and quantitative evidence that showed greater COVID-19 vaccine related mistrust in Black Americans compared to White Americans [ 11 , 12 , 24 , 25 ]. Consistent with prior literature on disparities related to the vaccination intentions for COVID-19 as well as seasonal influenza, HPV, and future HIV vaccines in Black Americans and other racial/ethnic minority groups [ 11 , 26 30 ], our data also showed substantial and multiple structural barriers to vaccination (e.g., transportation, financial, technology barriers that block vaccine access), as well as the negative impact of persistent systemic racism on vaccination intentions among Black Americans.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The current paper reports qualitative findings from semi-structured interviews with Black Americans who showed low vaccine confidence as well as stakeholders representing different Black communities during the early stage of the COVID-19 vaccine roll-out. We documented low COVID-19 vaccination intentions (e.g., the need to wait and see) and specific concerns around the COVID-19 vaccines (e.g., about rapid development and side effects), which are consistent with similar qualitative research in racially/ethnically diverse populations (including Black Americans) and quantitative evidence that showed greater COVID-19 vaccine related mistrust in Black Americans compared to White Americans [ 11 , 12 , 24 , 25 ]. Consistent with prior literature on disparities related to the vaccination intentions for COVID-19 as well as seasonal influenza, HPV, and future HIV vaccines in Black Americans and other racial/ethnic minority groups [ 11 , 26 30 ], our data also showed substantial and multiple structural barriers to vaccination (e.g., transportation, financial, technology barriers that block vaccine access), as well as the negative impact of persistent systemic racism on vaccination intentions among Black Americans.…”
Section: Discussionsupporting
confidence: 73%
“…Participants and stakeholders in the present study also identified system intervention strategies, from acknowledging systemic racism and improving the trustworthiness of institutions to preferred messaging contents, information sources and mode, and access points. While there were some novel ideas (e.g., discussing vaccination as empowerment), many of these strategies are consistent with the extant literature on strategies to increase COVID-19 vaccination update in Black communities and other racial/ethnic minority populations [ 11 , 12 ] as well as strategies to acknowledge medical mistrust in other health conditions such as HIV [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The population groups most heavily affected by COVID-19 each require tailored interventions that address group-specific concerns [ 62 ]. For undocumented immigrants, this review highlights that the prominent issues around low vaccine uptake were less frequently attributed to medical mistrust which elsewhere in the literature was more often discussed as prominent for non-immigrant Black communities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is significant concern that the COVID-19 pandemic will exacerbate already existing health inequities between foreign residents and citizens ( Caron & Adegboye, 2021 ). Immigrants are more likely to experience COVID-19-related health disruptions because of crowded housing and large household size ( Kjollesdal et al, 2022 ), difficulty with health literacy ( Wang et al, 2020 ), concerns related to testing and treatment (e.g., requirements to present official identification or residency documentation) ( Lechuga et al, 2022 ), language barriers ( Caron & Adegboye, 2021 ), and inadequate insurance coverage ( McFadden et al, 2022 ). Furthermore, a multi-country analysis has shown that the threat posed by COVID-19 has led to increased “othering” of immigrant communities and anti-immigrant sentiment ( Mula et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%